Pengaruh Faktor Fundamental Ekonomi Makro Terhadap Harga Saham Di Jakarta Islamic Index (JII) Tahun 2019-2022 - Windytiafitli, Rizka (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
The capital market has an important role and is a benchmark for economic progress in a country. The capital market is used as a forum or means for investors to make long-term investments. The Jakarta Islamic Index (JII) is an index used as a benchmark to measure the performance of an investment in sharia-compliant stocks. In investing in stocks, an investor pays attention to the factors that affect the price of the shares he will buy. There are macroeconomic fundamental factors that are thought to influence stock prices. This study aims to determine the influence of any factors that influence macroeconomic fundamental factors on stock prices in the Jakarta Islamic Index (JII). Researchers limit the issues to be discussed only on inflation, interest rates, exchange rates, money supply and gross domestic product (GDP). This study uses a statistical approach to panel data which is processed through E-Views 12, namely quantitative method analysis. The amount of data is 336 data. The samples used are several stocks in the Jakarta Islamic Index (jii) 30, namely PT Adaro Energy Tbk (ADRO), PT AKR Corporindo Tbk (AKRA), PT Indofood CBP Sukses Makmur Tbk (ICBP), PT Kalbe Farma Tbk (KLBF) , PT Telkom Indonesia (Persero) Tbk (TLKM), PT United Tractors Tbk (UNTR), PT Unilever Indonesia Tbk (UNVR), data taken from 2019-2022 in the form of monthly data. Partially, the results show that inflation and interest rates have no effect, while the exchange rate, money supply and GDP have an effect on stock prices in JII. Simultaneously these five variables have an influence on stock prices in JII.